COLOUR PSYCHOLOGY AND CREATIVE EXPRESSION OF THE INDIAN ARTISTS COMMUNITY - Sharma, Mani Nandini; Mazumder, Marriena (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Art functions as a unique mode of perception that offers extraordinary ways of engaging with reality beyond mere aesthetic decoration, while an artist creates meaning through the thoughtful and skilful combination of elements in their contemporary art practices. Colour, as a fundamental component of human visual experience, carries psychological and symbolic significance that shapes emotions, perceptions, and behaviour. This study examines the role of colour psychology in contemporary art practice, focusing on how artists employ colour to process emotional states, and how these choices affect spectators. Using a qualitative research framework, the study draws on in-depth interviews with contemporary artists, alongside critical analysis of artworks, written documentation, and verbal narratives. The findings indicate that artists frequently project emotional and psychological states onto the canvas, using colour to translate abstract moods into tangible visual forms. This research addresses that gap by integrating psychological, artistic, and experiential perspectives. The study concludes that colour psychology plays a critical role in art-making, offering valuable insights for artists, practitioners, students, and future interdisciplinary research.